-6g-9=-5g

Simple and best practice solution for -6g-9=-5g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6g-9=-5g equation:



-6g-9=-5g
We move all terms to the left:
-6g-9-(-5g)=0
We get rid of parentheses
-6g+5g-9=0
We add all the numbers together, and all the variables
-1g-9=0
We move all terms containing g to the left, all other terms to the right
-g=9
g=9/-1
g=-9

You can always share this solution

See similar equations:

| 1-2b=-4b+10+3b | | -9+v=7v+9 | | -10-6k=-8k+10 | | 1.2+z=3.2 | | 4(x-3)+20=3(x=4) | | -9+9q=1+10q | | -12+x/2=2 | | -6m=-3m-9 | | -7-9p=-10p | | 7x=-51+9 | | 2j+9=-j | | X(3.44)+x(4.33)=49.29 | | 9-4t=-3t | | x-7.5=16.4 | | m?5=180°-81°=99° | | -1.3x+7=31 | | 0.04x=0.01 | | (2x-7)(6x+7)=0 | | 3x-2/3x=3/14 | | 48p=12 | | 0=-4.9t^2+9.8t | | -11-x=-17 | | 48÷p=12 | | 14x-1=-57 | | 9*x+1/7=18 | | 5x-2=-4x+12 | | 14x–61=2x+35 | | 2x+35=14x–61 | | 134=5x+84 | | 5(x-5)-x=4x | | 67=5x+84 | | x+34=11x-56 |

Equations solver categories